Interlocution of knowledge: The cognitive principles of complexity in the pedagogical thought of Mario Osorio Marques (Revista Contexto & Educação, 2025)
Did Mario Osorio Marques flirt with Edgar Morin? Did Marques make any incursions into the ontological-epistemological matrix of complex thought? The aim of this theoretical essay is to show that Marques, in his pedagogical thinking, sought to distinguish the paradigms of the object, the subject and intersubjectivity, but his main concern was to understand them in an integrated way in a “broader and more coherent theoretical framework”, which can be understood by the term “interlocution of knowledge”. In addition to this objective, the intention is to point out evidence that Marques transcends the simple framing in a single paradigm and that, systematically, he placed in dialogue the empirical-analytical, historical-hermeneutic and critical-dialectical approaches, in the broader theoretical framework of communicative reason and, through a circular and progressive form of thought, he narrowed the dialogue with the principles of intelligibility of what he called the “paradigm of complexity”. Therefore, an epistemological reading of his writings from the period from 1988 to 2002 is proposed. The theoretical essay is structured in three movements. The first one considers the ontological and gnosiological assumptions of Marques' educational praxis. In a second movement, we seek the presence of evidence of an alternative scientific paradigm for the science of the educator, in Marques' work. Finally, the presence of the principles of intelligibility of complex thought in Marques' proposal for training education professionals is discussed. Our reading of Marques' work led us to assume that it was the problem of interdisciplinarity that attracted him, sometimes to the edges, sometimes to the interior of the paradigm of complexity.
Keywords: Mario Osorio Marques; Rationalities; Pedagogy; Science of the educator